Effects of Ultraprotective Ventilation, Extracorporeal Carbon Dioxide Removal, and Spontaneous Breathing on Lung Morphofunction and Inflammation in Experimental Severe Acute Respiratory Distress Syndrome. (March 2015) - Güldner, Andreas; Kiss, Thomas; Bluth, Thomas; Uhlig, Christopher; Braune, Anja; Carvalho, Nadja; Quast, Theresa; Rentzsch, Ines; Huhle, Robert; Spieth, Peter; Richter, Torsten; Saddy, Felipe; et al.
Abstract : Background: To investigate the role of ultraprotective mechanical ventilation (UP-MV) and extracorporeal carbon dioxide removal with and without spontaneous breathing (SB) to improve respiratory function and lung protection in experimental severe acute respiratory distress syndrome. Methods: Severe acute respiratory distress syndrome was induced by saline lung lavage and mechanical ventilation (MV) with higher tidal volume (VT ) in 28 anesthetized pigs (32.8 to 52.5 kg). Animals (n = 7 per group) were randomly assigned to 6 h of MV (airway pressure release ventilation) with: (1) conventional P-MV with VT ≈6 ml/kg (P-MVcontr ); (2) UP-MV with VT ≈3 ml/kg (UP-MVcontr ); (3) UP-MV with VT ≈3 ml/kg and SB (UP-MVspont ); and (4) UP-MV with VT ≈3 ml/kg and pressure supported SB (UP-MVPS ). In UP-MV groups, extracorporeal carbon dioxide removal was used. Results: The authors found that: (1) UP-MVcontr reduced diffuse alveolar damage score in dorsal lung zones (median[interquartile]) (12.0 [7.0 to 16.8] vs. 22.5 [13.8 to 40.8]), but worsened oxygenation and intrapulmonary shunt, compared to P-MVcontr ; (2) UP-MVspont and UP-MVPS improved oxygenation and intrapulmonary shunt, and redistributed ventilation towards dorsal areas, as compared to UP-MVcontr ; (3) compared to P-MVcontr, UP-MVcontr and UP-MVspont, UP-MVPS yielded higher levels of tumor necrosis factor-α (6.9 [6.5 to 10.1] vs. 2.8 [2.2 to 3.0], 3.6 [3.0 to 4.7] and 4.0 [2.8 to 4.4] pg/mg, respectively) and interleukin-8 (216.8 [113.5 to 343.5] vs. 59.8 [45.3 to 66.7], 37.6 [18.8 to 52.0], and 59.5 [36.1 to 79.7] pg/mg, respectively) in dorsal lung zones. Conclusions: In this model of severe acute respiratory distress syndrome, MV with VT ≈3 ml/kg and extracorporeal carbon dioxide removal without SB slightly reduced lung histologic damage, but not inflammation, as compared to MV with VT = 4 to 6 ml/kg. During UP-MV, pressure supported SB increased lung inflammation. Abstract : In a model of severe acute respiratory distress syndrome in pigs, mechanical ventilation with 3 ml/kg tidal volume and extracorporeal carbon dioxide removal without spontaneous breathing slightly reduced lung histologic damage. Spontaneous breathing during ultraprotective ventilation improved gas exchange and distribution of ventilation, but pressure support increased lung inflammation.